2020
DOI: 10.1038/s41398-020-0759-0
|View full text |Cite
|
Sign up to set email alerts
|

Stress, inflammation and hippocampal subfields in depression: A 7 Tesla MRI Study

Abstract: Experiencing stressful events throughout one's life, particularly childhood trauma, increases the likelihood of being diagnosed with Major Depressive Disorder (MDD). Raised levels of cortisol, and markers of inflammation such as Interleukin (IL-6) and C-reactive protein (CRP), have been linked to both early life stress and MDD. We aimed to explore the biological stress signatures of early stress and MDD on hippocampal sub regional volumes using 7 Tesla MRI imaging. A cohort of 71 MDD patients was compared agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…One factor that might explain why our BD patients revealed no major hippocampal volume reductions is that, differently from ours, their cohort was heterogeneous, and not characterized by a predominantly depressive subtype. Our results, however, support the findings from a recent investigation showing no smaller volumes in MDD patients via high-resolution 7-Tesla MRI (Tannous et al, 2020 ). As in this study only HippSub volumes and not shape alterations were assessed, therefore we cannot identify if HippSub deformations coinciding with unaltered volumes were seen, as has been reported in MDD (Ballmaier et al, 2008 ; Cole et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…One factor that might explain why our BD patients revealed no major hippocampal volume reductions is that, differently from ours, their cohort was heterogeneous, and not characterized by a predominantly depressive subtype. Our results, however, support the findings from a recent investigation showing no smaller volumes in MDD patients via high-resolution 7-Tesla MRI (Tannous et al, 2020 ). As in this study only HippSub volumes and not shape alterations were assessed, therefore we cannot identify if HippSub deformations coinciding with unaltered volumes were seen, as has been reported in MDD (Ballmaier et al, 2008 ; Cole et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
“…CA, Cornu ammonis; DG, dentate gyrus; SUB, subiculum; Tail, hippocampal tail; ERC, entorhinal cortex. For segmentation display, please see https://www.nitrc.org/projects/ashs 1.5T or 3T MRI, with four studies (9%) using high-field 7T MRI (Brown et al, 2019;Kraus et al, 2019;Tannous et al, 2020;Wisse et al, 2015).…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…23 A large sample study showed a larger hippocampal tail in patients with MDD than in healthy controls, 20 and a 7 T MRI study failed to detect any volume abnormalities in hippocampal subfields. 71 These inconsistencies in the results may be because of the heterogeneity inherent in mood disorders (related to illness duration and treatment effects) probably along with less robust and more limited findings of hippocampal alterations in patients with MDD. Greater hippocampal atrophy in the parasubiculum and HATA in patients with schizophrenia relative to patients with MDD may contribute to the distinct clinical presentations associated with the 2 disorders.…”
Section: E45mentioning
confidence: 99%